Biomorphic changes versus the secular trend in man - Sikora, Paweł (Anthropological Review, 1976)
The author studied changes in body height, longth and breadth of the head, height and breadth of the face, as well as height and breadth of the nose, in human age groups. The material for this investigation was taken from Southern Poland and Egypt. Materials of so far distant areas were used in order to determine whether the occurence of differences in the bodily dimensions with age exhibit the same trend in both cases. A similar trend of the morphological changes in adults in either group would suggest that this same phenomenon occurs in other populations as well.The results obtained show that the considered body dimensions of adults change with age and exhibit a definite trend. For example, the body height decreases, the head and face dimensions generally increase.The changes occurring in the age groups are interpreted by the author not only as biomorphotical changes but also as due to the phenomenon of secular trend.